2022
DOI: 10.1186/s12904-022-01005-3
|View full text |Cite
|
Sign up to set email alerts
|

The development and feasibility study of Multidisciplinary Timely Undertaken Advance Care Planning conversations at the outpatient clinic: the MUTUAL intervention

Abstract: Background Patients still receive non-beneficial treatments when nearing the end of life. Advance care planning (ACP) interventions have shown to positively influence compliance with end of life wishes. Hospital physicians seem to miss opportunities to engage in ACP, whereas patients visiting the outpatient clinic usually have one or more chronic conditions and are at risk for medical emergencies. So far, implemented ACP interventions have had limited impact. Structural implementation of ACP ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The MUTUAL ACP intervention consists of four steps: timely patient selection, the patient and healthcare professionals preparing for the conversation, a scripted ACP conversation in a multidisciplinary setting (a trained nurse starting the conversation and the treating physician joining the conversation) and documentation of the conversation. An elaborate description of the development and feasibility study of the MUTUAL intervention can be found elsewhere [ 4 ]. A questionnaire was developed for patients to complete prior to the conversation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MUTUAL ACP intervention consists of four steps: timely patient selection, the patient and healthcare professionals preparing for the conversation, a scripted ACP conversation in a multidisciplinary setting (a trained nurse starting the conversation and the treating physician joining the conversation) and documentation of the conversation. An elaborate description of the development and feasibility study of the MUTUAL intervention can be found elsewhere [ 4 ]. A questionnaire was developed for patients to complete prior to the conversation.…”
Section: Methodsmentioning
confidence: 99%
“…The Multidisciplinary Timely Undertaken Advance Care Planning (MUTUAL) intervention was developed in 2018 [ 4 ]. An important element of the MUTUAL intervention is that a trained nurse starts the conversation, and is joined by the treating physician in the second part of the conversation.…”
Section: Introductionmentioning
confidence: 99%
“…Outpatient clinics provide an opportune environment for end-of-life treatment discussions in a less stressful setting. 7 Adapting ACP interventions to address barriers in the clinical setting has been identified as a key strategy for effective implementation. 8 Advance care planning interventions that target individual, service and system-level processes simultaneously may result in improved ACP uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Outpatient clinics provide an opportune environment for end‐of‐life treatment discussions in a less stressful setting 7 . Adapting ACP interventions to address barriers in the clinical setting has been identified as a key strategy for effective implementation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have assessed ACP implementation in tertiary outpatient settings. Two studies, assessing one multicomponent intervention, found the intervention to be feasible and acceptable from the perspective of HCPs (van Lummel et al, 2022(van Lummel et al, , 2023. Patient and family perceptions of ACP intervention and the extent to which this differs from current care provided in outpatient settings remains unclear.…”
Section: Introductionmentioning
confidence: 99%